Targeted Neonatal Echocardiography Services: Need for Standardized Training and Quality Assurance. (1st October 2014) - Finan, Emer; Sehgal, Arvind; Khuffash, Afif El; McNamara, Patrick J.
Abstract : Objectives: Targeted neonatal echocardiography refers to a focused assessment of myocardial performance and hemodynamics directed by a specific clinical question. It has become the standard of care in many parts of the world, but practice is variable, and there has been a lack of standardized training and evaluation to date. Targeted neonatal echocardiography was first introduced to Canada in 2006. The purpose of this study was to examine the characteristics of targeted neonatal echocardiography practice and training methods in Canadian neonatal intensive care units (NICUs). Methods: A total of 142 Canadian neonatologists were invited to participate in an online survey, which was conducted in September 2010. The survey consisted of questions related to the availability of targeted neonatal echocardiography, clinical indications, benefits and risks, and training methods. Results: The overall survey response rate was 65%. Forty‐eight respondents (34%) indicated that targeted neonatal echocardiography was available in their units, and the program was introduced within the preceding 1 to 5 years. In centers where it was unavailable, lack of on‐site echocardiography expertise was cited as the major barrier to implementation. The most common indications for targeted neonatal echocardiography included evaluation of a hemodynamically significant ductus arteriosus, systemic or pulmonary blood flow, and response to cardiovascular treatments. Only 27% of respondents, working in centers where targeted neonatal echocardiography existed, actually performed the studies themselves; most individuals completed 11 to 20 studies per month. Almost half of the respondents said that training was available in their institutions, but methods of training and evaluation were inconsistent. Eighty‐seven percent of respondents reported no formalized process for assessment of ongoing competency after the initial training period. Conclusions: Targeted neonatal echocardiography is becoming more widely available and is gaining acceptance in Canadian NICUs. Although training is provided in many institutions, the process is not well established, and formal evaluation is rarely performed. This study emphasizes the need for development of standards for formalized training, evaluation, and quality assurance.